Pengaruh Stimulasi Media Gambar Kartun Indonesia Terhadap Karakter Building Kedisiplinan Memilah Sampah Pada Anak Usia Dini Usia 4-6 Tahun Di PAUD Kecamatan Gamping Kabupaten Sleman - Yustiana Olfah; Ni Ketut Mendri; Bambang Suwerda (POLTEKKES KEMENKES YOGYAKARTA, 2017)
Discipline attitude in maintaining the environment cleanliness, especially in sorting garbage should be introduced at an early age1. The essence of early education is to provide some stimulation in order to optimize all children potential (body / physical or spiritual / mental), including the sorting of garbage that has not been optimally done in early childhood. There are many kinds of stimulation techniques for character education in early childhood, through sound, music, movement, touch, talking, singing, reading, matching, comparing, classifying, solving problems, scribbling, drawing, and stringing. The aim of this experiment is to determine the effect of stimulation of the picture media on character building discipline on sorting garbage at an early age children (4-6 years old) at Playgroup in Gamping, Sleman, Yogyakarta. The type of this research is Quasi Research with